Did the pandemic have an impact on influenza vaccination attitude? a survey among health care workers - Pullukçu Hüsnü; Taşbakan Meltem; Sipahi Oğuz; Yamazhan Tansu; Durusoy Raika; Arda Bilgin; Erdem Esra; Ulusoy Sercan (BMC Infectious Diseases, 2011)
Abstract Background Health care workers' (HCWs) influenza vaccination attitude is known to be negative. The H1N1 epidemic had started in mid 2009 and made a peak in October-November in Turkey. A national vaccination campaign began on November 2nd, 2009. Despite the diligent efforts of the Ministry of Health and NGOs, the attitudes of the media and politicians were mostly negative. The aim of this study was to evaluate whether HCWs' vaccination attitudes improved during the pandemic and to assess the related factors. Methods This cross-sectional survey was carried out at the largest university hospital of the Aegean Region-Turkey. A self-administered questionnaire with 12 structured questions was applied to 807 HCWs (sample coverage 91.3%) before the onset of the vaccination programme. Their final vaccination status was tracked one week afterwards, using immunization records. Factors influencing vaccination rates were analyzed using ANOVA, t-test, chi-square test and logistic regression. Results Among 807 participants, 363 (45.3%) were doctors and 293 (36.6%) nurses. A total of 153 (19.0%) had been vaccinated against seasonal influenza in the 2008-2009 season. Regarding H1N1 vaccination, 143 (17.7%) were willing to be vaccinated vs. 357 (44.2%) unwilling. The number of indecisive HCWs was 307 (38.0%) one week prior to vaccination. Only 53 (11.1%) stated that they would vaccinate their children. Possible side effects (78%, n = 519) and lack of comprehensive field evaluation before marketing (77%, n = 508) were the most common reasons underlying unwillingness or hesitation. Among the 749 staff whose vaccination status could be tracked, 228 (30.4%) actually received the H1N1 vaccine. Some of the 'decided' staff members had changed their mind one week later. Only 82 (60%) of those willing, 108 (37%) of those indecisive and 38 (12%) of those unwilling were vaccinated. Indecisive HCWs were significantly younger (p = 0.017). Females, nurses, and HCWs working in surgical departments were more likely to reject vaccination (p < 0.05). Doctors, HCWs working in medical departments, and HCWs previously vaccinated against seasonal influenza were more likely to accept vaccination (p < 0.05). Being younger than 50 and having been vaccinated in the previous season were important predictors of attitude towards pandemic influenza vaccination. Conclusions Vaccination rates increased substantially in comparison to the previous influenza season. However, vaccination rates could have been even higher since hesitation to be vaccinated increased dramatically within one week (only 60% of those willing and the minority of those indecisive were finally vaccinated). We speculate that this may be connected with negative media at the time.